Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1353/hpu.2013.0033
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Prostate Cancer Education Intervention for Low-income African Americans: Impact on Knowledge and Screening

Abstract: African American men bear disproportionate burden of prostate cancer (PCa) that can be reduced by early detection. A 15-minute culturally appropriate PCa education intervention developed to communicate effective, relevant, and balanced PCa screening information to low-income African American men was evaluated in men 42 years and older who had not been screened in one year. Of 539 men enrolled, 392 (72.7%) completed the six-month follow-up. Mean age was 54.4±8.9, 34.7% had no high school diploma, and 65.3% earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…A recent study, Ukoli et al (2013) observed the impact of tailored prostate cancer education on knowledge and screening among 539 low-income African Americans men and found that 15-minutes education interventions (providing a prostate cancer brochure and tailored interaction) led to improved knowledge, beliefs, and action. Furthermore, researchers showed that a balanced educational intervention on the risks and benefits of prostate cancer screening helped provide a platform for participants to make informed decisions and dramatically increased PSA testing, among men who did not have access to regular physical examinations.…”
Section: )mentioning
confidence: 99%
“…A recent study, Ukoli et al (2013) observed the impact of tailored prostate cancer education on knowledge and screening among 539 low-income African Americans men and found that 15-minutes education interventions (providing a prostate cancer brochure and tailored interaction) led to improved knowledge, beliefs, and action. Furthermore, researchers showed that a balanced educational intervention on the risks and benefits of prostate cancer screening helped provide a platform for participants to make informed decisions and dramatically increased PSA testing, among men who did not have access to regular physical examinations.…”
Section: )mentioning
confidence: 99%
“…For example, CNP reports described culturally tailored interventions that resulted in reduced tobacco use among Asian immigrants 46 and Native Hawaiians. 47 They described CBPR projects that attracted rural dwelling adults to cancer screening for the first time 40 ; increased breast and cervical cancer screening among Vietnamese, Hmong, Micronesian, Hispanics, and African-American women 17,23,48–50 ; increased colorectal cancer screening among Chinese Americans, 44 Hispanics, 51,52 and African Americans 53 ; increased Pap test follow-up among American Indian women 54 ; increased hepatitis B immunization among Asian Americans 55 ; increased prostate cancer screening among African Americans 56,57 ; and increased minority participation in clinical trials. 58,59 …”
Section: Resultsmentioning
confidence: 99%
“…45 Likewise, the lack of health insurance as well as the cost for PCS have been identified as primary barriers to receiving PCS. 46 It is unfortunate that a lack of health facilities and educational awareness regarding PCa may be viewed as barriers to receiving PCS as well as additional health promotion and preventive services. 29 Talcott et al 32 reported AA males as being less likely to access and receive a consistent source of health care.…”
Section: Church Attendancementioning
confidence: 99%